Experimental systems for studying Plasmodium/HIV coinfection. Issue 13 (15th April 2016) - Frischknecht, Friedrich; Fackler, Oliver T.
Abstract : Coinfections with Human Immunodeficiency Virus (HIV) and Plasmodium, the causative agents of AIDS and malaria, respectively, are frequent and their comorbidity especially in sub‐Saharan Africa is high. While clinical studies suggest an influence of the two pathogens on the outcome of the respective infections, experimental studies on the molecular and immunological impact of coinfections are rare. This reflects the limited availability of suitable model systems that reproduce key properties of both pathologies. Here, we discuss key aspects of coinfection with a focus on currently established experimental systems, their limitations for coinfection studies and potential strategies for their improvement. Abstract :